Pengaruh Metode Pembelajaran Problem Solving terhadap Keterampilan Berpikir Kreatif Materi Penyajian Data Kelas V - Pramesti, Rima; Iqbal Amrillah, Nur; Sutriyani, Wulan (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
The lack of students' problem solving abilities and students' creative thinking skills is caused by several factors, including lack of precision in the selection and use of learning strategies and methods. The Problem Sloving Learning Method is considered suitable for training students in solving problems. The aim of this research is to determine the influence of the Problem Solving Method on mathematical creative thinking skills in class V data presentation material at SD N 03-04 Margoyoso and to determine the difference in the influence of mathematical creative thinking skills before and after applying the problem solving method to class data presentation material. V SD N 03-04 Margoyoso. This research uses a pre-experimental design method with a